Oyster grower perspectives on green crab (Carcinus maenas) interactions: using applied social science to inform research and engagement - Meyer-Rust, Kelsey; Williams, Lindsey; Ward, Krystin; Brown, Bonnie (Frontiers in Aquaculture, 2024)
Research that informs the New Hampshire Aquaculture industry, which has grown significantly over the past few years, and helps the overall associated watershed community to keep Great Bay Estuary healthy is vital. Specific study of green crabs, Carcinus maenas, and their potential effects on oysters, Crassostrea virginica, is important to gain a better understanding of the impact invasive species may have on these ecologically and economically important bivalves.The aim of this study was to document and understand New Hampshire (NH) oyster growers' perspectives on the issue of green crab predation of oysters. Through a survey, this study documented a preliminary understanding of farmer perspectives and research needs regarding the population of green crabs in NH waters. More specifically, this survey provided a social science perspective and information on areas of potential research -abundance, distribution, and diet of green crabs -that could be beneficial to the oyster industry. This study fills knowledge gaps, helps improve future research (including how to better engage with end users), and facilitates creating and implementing solutions that benefit the NH oyster aquaculture industry.